CNash - A novel parameter predicting cake solids of dewatered digestates. (1st July 2019) - Svennevik, Oda K.; Beck, Greeley; Rus, Ester; Westereng, Bjørge; Higgins, Matthew; Solheim, Odd Egil; Nilsen, Pål J.; Horn, Svein J.
Abstract: Efficient digestate dewatering is crucial to reduce the volume and transportation cost of solid residues from anaerobic digestion (AD) plants. Large variations in dewatered cake solids have been reported and predictive models are therefore important in design and operation of such plants. However, current predictive models lack validation across several digestion substrates, pre-treatments and full-scale plants. In this study, we showed that thermogravimetric analysis is a reliable prediction model for dewatered cake solids using digestates from 15 commercial full-scale plants. The tested digestates originated from different substrates, with and without the pre-AD thermal hydrolysis process (THP). Moreover, a novel combined physicochemical parameter (C/Nash) characterizing different digestate blends was identified by multiplying the C/N ratio with ash content of the dried solids. Using samples from 22 full-scale wastewater, food waste and co-waste plants, a linear relationship was found between C/Nash and predicted cake solids for digestates with and without pre-AD THP. Pre-AD THP improved predicted cake solids by increasing the amount of free water. However, solids characteristics like C/N ratio and ash content had a more profound influence on the predicted cake solids than pre-AD THP and type of dewatering device. Finally, C/Nash was shown to have a linear relationship to cake solids and reported polymer dose from eight full-scale pre-AD THP plants. In conclusion, we identified the novel parameter C/Nash which can be used to predict dewatered cake solids regardless of dewatering device and sludge origin. Graphical abstract: Image 1 Highlights: Full-scale dewatered cake solids were predicted by thermogravimetric analysis. Digestates were described by the C/N ratio and ash content (C/N.ash) Dewatered cake solids can be predicted from C/N.ash Thermal hydrolysis increased predicted cake solids.